Особливості вивчення механізмів вогнищ землетрусів графічним методом у районі Середземномор’я - Малицький, Д.В.; Грицай, О.Д.; Муйла, О.О.; Кутнів, О.І.; Обідіна, О.О.; Асташкіна, О.А.; Павлова, А.Ю.; Козловський, Е.М. (Геоінформатика, 2015)
Розглянуто задачу визначення механізму вогнища землетрусу та вплив швидкісної моделі середовища на її розв’язання. Для розв’язання цієї задачі запропоновано графічний метод, за допомогою якого побудовано механізми вогнищ двох землетрусів у районі Середземного моря. Показано важливість вибору коректної моделі середовища та її вплив на значення кута виходу прямої P-хвилі як одного з основних параметрів у графічному методі, особливо в разі малої кількості сейсмічних станцій, що зареєстрували подію. Для визначення механізмів вогнищ використано інформацію про нечіткі вступи P-хвилі на вертикальній компоненті сейсмічного запису. Отримано результати щодо параметрів фокальних механізмів розглянутих землетрусів, ці параметри порівняно з параметрами фокальних механізмів, визначеними іншими методами. Рассмотрены задача определения механизма очага землетрясения и влияние скоростной модели среды на ее решение. Предложен графический метод, с помощью которого построены механизмы очагов двух землетрясений в районе Средиземного моря. Показаны важность выбора правильной модели среды и ее влияние на значение угла выхода, одного из основных параметров в графическом методе, особенно в случае малого количества сейсмических станций, зарегистрировавших событие. Для определения механизмов очагов использована информация о нечетких вступлениях Р-волны на вертикальной компоненте сейсмической записи. Приведено сравнение полученных значений параметров фокальных механизмов рассмотренных землетрясений с параметрами фокальных механизмов, определенными другими методами. Purpose. The purpose of this paper is to show the effectiveness of the graphic method to solve the problem of determining the focal mechanisms of earthquakes and also to define the impact of the velocity model on the problem solution with a small number of stations. The focal mechanisms of earthquakes in the Mediterranean area were determined: 24.04.2011, 13:02:12,00 near Malta φ = 35,92°, λ = 14,95°, h = 10 km Ml = 4,1 and 29/12/2013, 17:08:43,00 in Italy φ = 41,369°, λ = 14,445°, h = 10,5 km, Ml = 4,9. The obtained results were compared with the known focal mechanisms of these earthquakes. Design/methodology/approach. To determine the focal mechanism of earthquakes, the graphic method based on the polarity of the first arrival of P-waves was applied, as well as the information on fuzzy arrivals of P-waves and the S/P- wave amplitude ratio. Findings. The focal mechanism parameters of the two earthquakes in the Mediterranean Sea have been obtained. By determining one of the focal mechanisms, we demonstrated the impact of the velocity model on the important parameter necessary build up the focal mechanism by using graphic method — the take off angle. Practical value/implications. The paper proves the effectiveness of the graphic method to determine the focal mechanisms since the results obtained by the graphic method and other methods are close we have demonstrated. The importance of the information on fuzzy arrivals of direct P waves at stations closely correlated as well as the choice of a velocity model. The development of the graphic method and its modifications may be applied to determine the focal mechanisms of earthquakes in the Carpathian region.